Urgensi Pendidikan Seks di Sekolah Mencegah Bukan Mengajarkan: Membangun Generasi Muda yang Sehat dan Bertanggung Jawab - Cut Kumala Sari; Melianda Futri; Delima Putri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Sex education in schools is an important aspect in supporting the growth and development and reproductive health of children and adolescents. However, in Indonesia, there is cultural resistance regarding the open discussion of sex education. Sex education in schools plays an important role in shaping the character and knowledge of adolescents regarding reproductive health, responsible sexual behavior, and prevention of various risks such as HIV/AIDS, premarital pregnancy, and sexually transmitted diseases. This article reviews the importance of sex education as an integral part of the school curriculum, with an approach to preventing deviant behavior and building a healthy and responsible young generation. It is hoped that through appropriate education, adolescents will be able to make wise and responsible decisions, and reduce the number of incidents that are detrimental to them. This discusses the urgency of implementing sex education in schools with a preventive approach, not just theoretical teaching. Preventive sex education aims to equip students with the knowledge, attitudes, and skills to maintain reproductive health, prevent unwanted pregnancies, sexually transmitted diseases, and sexual violence. The implementation of sex education that is appropriate to the cultural context and involves various stakeholders in schools is crucial in creating an inclusive and safe learning environment.